2016
DOI: 10.1177/1687814016662561
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical analysis of Norsorex/acrylonitrile butadiene rubber blends and their application in vibration control of steel frames

Abstract: The damping properties of acrylonitrile butadiene rubber/Norsorex Ò blends were investigated by dynamic mechanical analysis. The effects of Norsorex on the damping properties of acrylonitrile butadiene rubber/Norsorex blends were also studied. The results showed that 30-phr Norsorex could dramatically improve the damping of 70-phr acrylonitrile butadiene rubber. Compared with acrylonitrile butadiene rubber, the LA value of acrylonitrile butadiene rubber/ Norsorex = 70/30 increased to 7.3 3 10 8 from 3.0 3 10 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Myslivets et al 6 determined the vibration-isolating characteristics and measured the static and dynamic moduli of the natural rubber. Xu et al 7 investigated the damping properties of the acrylonitrile butadiene rubber. Gao and Zhang 8 used the finite element (FE) method to study the low frequency and broadband acoustic absorption below 1000 Hz of the viscoelastic damping rubber.…”
Section: Introductionmentioning
confidence: 99%
“…Myslivets et al 6 determined the vibration-isolating characteristics and measured the static and dynamic moduli of the natural rubber. Xu et al 7 investigated the damping properties of the acrylonitrile butadiene rubber. Gao and Zhang 8 used the finite element (FE) method to study the low frequency and broadband acoustic absorption below 1000 Hz of the viscoelastic damping rubber.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic mechanical analysis (DMA) showed that the temperature range of effective damping (tanδ ≥ 0.3) of vulcanized PNR was about 113 • C, and this range decreases as the EPDM content in the mixture increases. The PNR/EPDM vulcanizate at a ratio of 25/75 phr has a tanδ value at the point of maximum (tanδ max = 1.62) at a temperature of −34 • C. The work [37] describes the damping properties of rubber based on nitrile-butadiene rubber (NBR) and PNB (Norsorex ® ). The DMA results showed that Norsorex at 30 phr in 70 phr NBR significantly improved the damping characteristics of the vulcanizate based on them.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers derived from ring-opening metathesis polymerization (ROMP) are industrially important elastomers (e.g., Norsorex) and thermosets. A challenge with thermoset polymers is their poor solubility and processability, in part due to their cross-linked networks exactly the characteristics that present challenges for traditional molecular weight characterization methods but that we envisioned would be well-suited to FLIM methods.…”
mentioning
confidence: 99%